UNDERREPRESENTATION OF DISADVANTAGED YOUTH IN GIFTED PROGRAMS AND OVERREPRESENTATION IN PRISONSUNDERREPRESENTATION OF DISADVANTAGED YOUTH IN GIFTED PROGRAMS AND OVERREPRESENTATION IN PRISONS - Baldridge, Gregory (Acta Scientiae et Intellectus, 2024)
The United States of America has the highest incarceration rate in the world. The probability of an individual being incarcerated is a complex combination of factors, including socio-economic status, level of education, and ethnicity. Within prison populations, the percentage of individuals identified as gifted is higher than those identified within the general population. A lack of support for gifted individuals in their academic careers, both in the school system and in extracurricular opportunities, leads to a correlation in the higher number of gifted individuals in prison. When opportunities and supports are limited or non-existent, the potential for risk taking and incarceration is increased. Once an individual is incarcerated, there are a few programs to support general education needs; although, very few programs support the needs of gifted individuals. Using contemporary research on disadvantaged gifted students and gifted rates among prison populations, this paper provide an overview of these concerns and a call for s future investigations into the link between an increased rate of servicing gifted students’ needs and a possible reduced incarceration rate.